Energy demands in well-trained alpine ski racers during different duration of slalom and giant slalom runs - Bottollier, V.; Coulmy, N.; Le Quellec, L.; Prioux, J. (The Journal of Strength and Conditioning Research, 2020)
The purpose of this study was to investigate the energy demands of different duration slalom (SL) and giant slalom (GS) events in well-trained alpine ski racers. Eight well-trained alpine ski racers (age: 18.2 ± 0.8 years; stature: 1.72 ± 0.10 m; body mass: 65.8 ± 12.0 kg) performed an incremental laboratory test on cycle ergometer and 4 standardized alpine ski runs: short (ST) and long (LG) versions of SL and GS (SLST, SLLG, GSST, and GSLG). Oxygen uptake (Vo2) and heart rate (HR) were recorded continuously in all conditions. Blood lactate ([La]) was determined immediately before run and 3 and 5 minutes after run ([La]peak). The contribution of aerobic, glycolytic, and phosphagen energy systems was estimated. The aerobic system was the primary energy system involved in GSST (43.9 ± 5.7%) and GSLG (48.5 ± 2.5%). No significant difference in the contribution of aerobic and glycolytic systems was observed in SLST and SLLG. [La]peak was higher in SLLG (11.10 ± 2.41 mmol·L-1) than in GSST (8.01 ± 2.01 mmol·L-1). There was no difference in oxygen uptake peak between GSST and GSLG. Energetic training goals should focus on the improvement of both aerobic, glycolytic, and phosphagen systems for alpine ski racers who perform SL and GS. Giant slalom specialists might benefit from emphasizing the improvement of the aerobic system, without neglecting other systems.